High incidence of disease recurrence after discontinuation of disease-modifying antirheumatic drug treatment in patients with psoriatic arthritis in remission. Issue 4 (12th December 2013) - Araujo, Elizabeth G; Finzel, Stephanie; Englbrecht, Matthias; Schreiber, Dominik A; Faustini, Francesca; Hueber, Axel; Nas, Kemal; Rech, Juergen; Schett, Georg
Abstract : Objective: To investigate the possibility of drug-free remission in patients with psoriatic arthritis (PsA) in continuous remission. Methods: Prospective observational study in disease-modifying antirheumatic drug (DMARD)-treated PsA patients in continuous disease remission (no musculoskeletal symptoms, no or minimal skin/nail disease) for at least 6 months. Demographic, disease-specific and ultrasound parameters were assessed at baseline. DMARDs (traditional or biologic) were discontinued at the initial visit, and patients were followed for a maximum of 6 months for recurrence of disease. Results: 26 patients (methotrexate monotherapy: N=14; tumour necrosis factor inhibitors: N=12) with a mean age of 55.2 years, absence of musculoskeletal symptoms and minimal skin disease (mean Psoriasis Area Severity Index (PASI): 0.21) were enrolled. Incidence of recurrence of disease was high (N=20, 76.9%) and occurred rapidly (74.50±51.72 days) after treatment discontinuation. Male PsA patients were significantly more likely to lose remission. Long disease duration, more severe skin involvement and the presence of synovial hypertrophy by ultrasonographic examination at baseline decreased the likelihood for drug-free remission. Reinitiation of DMARDs promptly restored remission in all PsA patients with recurrence of disease. Conclusions: This study shows that the chance to reach drug-free remission in PsA patients is low. Discontinuation of DMARD therapy cannot be recommended in patients with PsA.